Numerical Study on the Shear Failure and Load Transfer Mechanism of Helical Piles in Cohesionless Soils under Axial Compressive Loading - Pratama, Ignatius Tommy; Lestari, Anastasia Sri; Oktavianus, Ivan (Journal of the Civil Engineering Forum, 2024)
The methods employed to calculate the axial bearing capacity of a helical pile depends on the shear failure model around the pile, which is also influenced by the spacing and diameter of the helical plates. However, studies on the transition of the failure mode and the load transfer mechanism with the change of helical plate spacing and diameter in cohesionless soil subjected to axial compressive load have been limited. Thus, this paper investigated the effects of helix diameter and spacing on the axial compressive load-bearing capacity, shear failure model, and load transfer mechanism of helical piles with two helical plates embedded in the homogeneous medium and dense sands, as well as in the stratified medium to very dense sand. Axial loading tests on helical piles with various helix diameters and spacings were simulated using a two-dimensional finite element program with axisymmetric modeling to obtain the load-settlement curve, which was later used to estimate the ultimate bearing capacity of the helical piles. The ultimate bearing capacity of the helical piles was also computed using the conventional methods, i.e., the individual bearing and cylindrical shear methods, and then compared to the numerical-based axial bearing capacity. The stress-strain behaviors of pile and soil were modeled using the Linear Elastic and Mohr-Coulomb material models, respectively. The results show that the numerical-based ultimate bearing capacity of a helical pile increased with increasing the diameter and spacing of the helix. However, the ultimate bearing capacity computed using conventional methods did not show this trend. Then, the transition from the cylindrical shear to the individual bearing failure mechanism occurred at a spacing ratio (i.e., helical plate spacing divided by its diameter) of about two. Ultimately, the load transfer curves indicate that the helical plates mainly supported the applied load.